Competency needs of extension agents in disseminating weather fore-cast information in Kwara state, Nigeria - L, Abdulrahman, O.; O, Ifabiyi, J.; S, Salami, O.; T, Ibrahim, M. (Journal of Kerbala for Agricultural Sciences, 2023)
Agricultural extension agents play crucial roles in the dissemination of innovation and enhancement of the productivity of the farmers in Nigeria. The research examined the competency needs of extension agents in Kwara State, Nigeria. About 117 extension agents were selected for the study. Statistical tools such as frequency count, percentage and mean score were used to analyse the data. The result revealed about 54.7 % of the respondents were male, the average age of the respondents was 44.9 years and the mean income of the respondents was 49461.38 Naira. The training sessions (̅mean=2.36) was most important source of information on weather forecast. The rainfall variability (MWDS= 0.458) was the highest ranked area of competency needs of extension agents. The inadequate facilities to disseminate weather forecast information (mean=2.38) was the most severe factor limiting dissemination of weather forecast information. The study recommended the provision of timely and accurate information on weather forecasts to the extension agents so that the farmers would make use of it at the right time.